2001
DOI: 10.2535/ofaj1936.78.1_17
|View full text |Cite
|
Sign up to set email alerts
|

Liver Sement S2 is Consistently Located at the Dorsal Side of S3 But Sometimes at the Right and/or Caudal Side of S3

Abstract: Summary: After preparing the frontal section including the origin of the left portal trunk at the hilar region, the left anatomical lobes of 111 human livers were dissected to reveal the segmental configuration based on the supplying portal vein branches. S2 was consistently located dorsal to S3. However, in contrast to the description in common textbooks for medical students, 19.8% of the specimens carried a paradoxical segmental configuration showing a "caudal and/or rightward" S2 in combination with a "cran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…S2 is called the lateral superior area, as described by Williams, 1995). In contrast, using specimens with simple bifurcation of the segmental branch of the portal vein P2 and P3, Wakiguchi et al . (2001) reported that S2 is consistently located dorsally to S3 but sometimes (19.8% in 111 livers) medially and/or caudally/inferiorly to S3 in contrast to the usual concept.…”
Section: Introductionmentioning
confidence: 99%
“…S2 is called the lateral superior area, as described by Williams, 1995). In contrast, using specimens with simple bifurcation of the segmental branch of the portal vein P2 and P3, Wakiguchi et al . (2001) reported that S2 is consistently located dorsally to S3 but sometimes (19.8% in 111 livers) medially and/or caudally/inferiorly to S3 in contrast to the usual concept.…”
Section: Introductionmentioning
confidence: 99%